Визначення поліхлорованих біфенілів (ПХБ) в оліях та жирах - Левчук, І. В. (НТУ "ХПІ", 2014)
Показана актуальность определения ПХБ в маслах и жирах. Показана актуальность определения ПХБ в маслах и жирах. Обоснована необходимость решения проблемы канцерогенной безопасности масложирових и жиросодержащих пищевых продуктах с надежным контролем стойких органических загрязнителей – полихлорированный бифенилов.

The actuality of determination of polychlorinated biphenyls (PCBs) in oils and fats is pointed. The necessity of solving the problem of carcinogenic safety of oils fats and fat con-taining food products with reliable control of sustainable organic pollutants polychlorinated biphenyls argumented.
Determination of polychlorinated biphenyls in the oils and fats
Keywords: рослинні олії; олії; стійкі органічні забруднювачі; поліхлоровані біфеніли